DETERMINAN KEPUTUSAN BERWIRAUSAHA LULUSAN SEKOLAH TINGGI ILMU EKONOMI CENDEKIA BOJONEGORO - Abdul Azis Safii (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
The purpose of this study is to examine the factors that influence entrepreneurial decisions in graduates of the Cendekia School of Economics. The research sample was 46 graduates who had become entrepreneurs or started businesses. Data were collected using a questionnaire that was distributed to respondents online and direct interviews. Data analysis using multiple linear regression techniques. The results showed that innovation and risk preference had a positive effect on the decision to become an entrepreneur. The motivation for achievement has a negative effect on the decision to become an entrepreneur. Meanwhile, entrepreneurship education and creativity do not affect the decision to become an entrepreneur.